THE EFFECT OF USING STORY PYRAMID STRATEGY ON READING COMPREHENSION OF STUDENTS OF SMP BABUSSALAM PEKANBARU - Yulisda, Nuraina; ', Eliwarti; ', Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This pre-experimental research is aimed to find out whether there is a significant effect of Story Pyramid strategy on reading comprehension of students of SMP Babussalam Pekanbaru. The design of the study is one group pretest-treatment-posttest design. The sample is VIII.6 chosen by using cluster random sampling technique. The results of the data analysis showed that the mean score of pre-test is 69.35 and the mean score of post-test is 77.83. In other words, the mean score of post-test is higher than pre-test. The value of t-test (9.575) is higher than t-table (2.074) at 5% of the significance level. Therefore, alternative hypothesis (Ha) is accepted and Null Hypothesis (Ho) is rejected. It could be concluded that there is a significant effect of using Story Pyramid strategy on improvement of reading comprehension of students of SMP Babussalam Pekanbaru.Keywords: Effect, Story Pyramid, Reading Comprehension, Narrative Texts.